2010
DOI: 10.1074/jbc.m109.098665
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vascular Endothelial Growth Factor-induced Endothelial Cell Migration by LIM Kinase 1-mediated Phosphorylation of Annexin 1

Abstract: In this study, we obtained evidence indicating that annexin 1 is a new target of the p38/MAPKAP kinase-2 pathway and that it regulates endothelial cell migration in response to vascular endothelial growth factor (VEGF). These conclusions are supported by a series of substantiating experiments. First, by twodimensional gel electrophoresis and mass spectrometry, we identified annexin 1 as a protein whose phosphorylation is induced by VEGF and is impaired by inhibiting p38. Second, using in vitro kinase assays an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…The mechanisms that underly the role of ANXA1 in regulating cell migration and angiogenesis are still ill defined. In endothelial cells, we found that phosphorylation of ANXA1 is required to trigger cell migration (7). Moreover, EGF-induced phosphorylation of ANXA1, triggers its colocalization with F-actin in the lamellipodia (23).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…The mechanisms that underly the role of ANXA1 in regulating cell migration and angiogenesis are still ill defined. In endothelial cells, we found that phosphorylation of ANXA1 is required to trigger cell migration (7). Moreover, EGF-induced phosphorylation of ANXA1, triggers its colocalization with F-actin in the lamellipodia (23).…”
Section: Discussionmentioning
confidence: 89%
“…ANXA1 is a calcium-and phospholipid-binding protein involved in regulating a broad range of cellular events, including migration in different types of cells such as myoblasts, leukemia, and breast cancer lines and endothelial cells (7,26,47,48). Moreover, a recent study showed that ANXA1 Ϫ/Ϫ mice are unable to heal the damage associated with indomethacin-induced gastric ulcers (30).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations